On the Issue of the Components of the Competency Model of a Teacher of a Higher Library School in the Conditions of Informatization - R. Z. Bogoudinova; S. D. Borodina; A. R. Mansurova; Yu. V. Maslova (Библиосфера, 2024)
The special competencies of a teacher at a higher library school are differentiated into actual pedagogical (methodological) and knowledge of library technology. In recent decades, the technology of working with documents and readers has been reduced in favor of activities such as marketing and management. In recent years, theorists and practitioners of librarianship have been unanimous in the opinion that the lack of such qualifications in the nomenclature of library positions has a negative impact on the status of young specialists and their retention in the library. The purpose of the article is to theoretically substantiate the elements of the competency model of a teacher of a higher library school under informatization. The authors propose a model of teacher professional competence, which is a set of professionally significant competencies developed taking into account the integration processes of education and ensuring not only professional, but also personal growth of the teacher